Hal-Hal yang Ada Hubungan dengan Kecacingan pada Anak di Beberapa Lokasi di Wilayah Indonesia periode Tahun 2005 sampai dengan Tahun 2020 - Asdihar, Nur; Rauf , Darmawaty; Nurliana , Nurliana (Bosowa Medical Journal, 2024)
Worms are infections of intestinal parasitic worms from the class of intestinal Nematodes that are transmitted through soil, or called Soil Transmitted Helminths (STH) consisting of roundworms (Ascaris Lumbricoides), whipworms (Trichiuris trichiura), and hookworms (Necator Americanus and Ancylostoma Duodenale). The purpose of this study was to find out the things that have a relationship with worms in children in several locations in Indonesia for the period 2005 to 2020. The research method is an analyticalresearch by synthesizing the results obtained by twelve scientific research journals with a case control research design. The results showed that there were things that had a relationship with worms in children in several regions in Indonesia, namely there was a significant relationship between hand washing habits (p value = 0.000), nail hygiene (p value = 0.000), use of footwear (p value = 0.000), contact with the ground (p value = 0.011), and mother's knowledge (p value = 0.000). against worms. So, helminthiasis in children in several locations in Indonesia for the period 2005 to 2020 has a significant relationship with hand washing habits, nail hygiene, use of footwear, contact with soil, and mother's knowledge